Morphological Diversity of Rattan on The Three Conservation Areas In South Sumatera - Baitika Baitika; Zulkifli Dahlan; Indra Yustian (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2018)
Research on the diversity of rattan morphology has been conducted in three forest conservation areas in South Sumatra i.e. Bentayan Wildlife Reserve, Bukit Cogong and Gunung Raya Wildlife Reserve. This study aims to analyze the diversity of rattan morphology in three protected areas in South Sumatra. This research uses purposive sampling method by exploring the forest area. The results showed that in the Bentayan Wildlife Reserve area were found 3 species of 3 genera while in Bukit Cogong Protected Forest were found 9 species of 3 genera and in the Bentayan Wildlife Reserve area were found 5 species of 3 genera. The morphology of rattans species in the three regions have different shapes and colors of thorns on the stem, the top and the bottom surfaces of the leaves, the climbing organ and the growth nature. The same rattan species were being found in the same of two or three locations, having morphological differences in diameter and length of the stem.